Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine the formula for the viscous force [tex]\( f \)[/tex] acting on a solid sphere moving through a liquid, we use dimensional analysis. The viscous force is found to depend on the coefficient of viscosity [tex]\( \eta \)[/tex], the radius [tex]\( M \)[/tex] of the sphere, and its speed [tex]\( U \)[/tex].
We will express [tex]\( f \)[/tex] as a function of [tex]\( \eta \)[/tex], [tex]\( M \)[/tex], [tex]\( U \)[/tex], and a proportionality constant [tex]\( k \)[/tex]:
[tex]\[ f = k \cdot \eta^a \cdot M^b \cdot U^c \][/tex]
### Step 1: Determine Dimensions of Each Quantity
1. Viscous Force [tex]\( f \)[/tex]:
- Dimension: [tex]\([f] = \text{MLT}^{-2}\)[/tex]
2. Coefficient of Viscosity [tex]\( \eta \)[/tex]:
- Dimension: [tex]\([\eta] = \text{ML}^{-1}\text{T}^{-1}\)[/tex]
3. Radius [tex]\( M \)[/tex]:
- Dimension: [tex]\([M] = \text{L}\)[/tex]
4. Speed [tex]\( U \)[/tex]:
- Dimension: [tex]\([U] = \text{LT}^{-1}\)[/tex]
### Step 2: Set Up Dimensional Equation
We need the dimensions on both sides of the equation [tex]\( f = k \eta^a M^b U^c \)[/tex] to be consistent. Thus,
[tex]\[ [f] = [k \eta^a M^b U^c] \][/tex]
Substituting the dimensions, we get:
[tex]\[ \text{MLT}^{-2} = [k] \cdot (\text{ML}^{-1}\text{T}^{-1})^a \cdot (\text{L})^b \cdot (\text{LT}^{-1})^c \][/tex]
### Step 3: Break Down the Dimensions
Combining the dimensions, we get:
[tex]\[ \text{MLT}^{-2} = \text{M}^a \cdot \text{L}^{-a} \cdot \text{T}^{-a} \cdot \text{L}^b \cdot \text{L}^c \cdot \text{T}^{-c} \][/tex]
Simplifying the dimensions, we have:
[tex]\[ \text{MLT}^{-2} = \text{M}^a \cdot \text{L}^{-a+b+c} \cdot \text{T}^{-a-c} \][/tex]
### Step 4: Equate the Exponents
Equating the exponents for [tex]\( \text{M} \)[/tex], [tex]\( \text{L} \)[/tex], and [tex]\( \text{T} \)[/tex] on both sides, we get three equations:
1. For mass (M):
[tex]\[ 1 = a \][/tex]
2. For length (L):
[tex]\[ 1 = -a + b + c \][/tex]
3. For time (T):
[tex]\[ -2 = -a - c \][/tex]
### Step 5: Solve the System of Equations
From the first equation:
[tex]\[ a = 1 \][/tex]
Substituting [tex]\( a = 1 \)[/tex] in the third equation:
[tex]\[ -2 = -1 - c \][/tex]
[tex]\[ -1 - c = -2 \][/tex]
[tex]\[ c = 1 \][/tex]
Substituting [tex]\( a = 1 \)[/tex] and [tex]\( c = 1 \)[/tex] in the second equation:
[tex]\[ 1 = -1 + b + 1 \][/tex]
[tex]\[ 1 = b \][/tex]
### Step 6: Write the Final Formula
Substituting [tex]\( a = 1 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = 1 \)[/tex] into our original expression [tex]\( f = k \eta^a M^b U^c \)[/tex], we obtain:
[tex]\[ f = k \eta^1 M^1 U^1 \][/tex]
Therefore, the formula for the viscous force [tex]\( f \)[/tex] is:
[tex]\[ f = k \eta M U \][/tex]
where [tex]\( k \)[/tex] is a dimensionless proportionality constant.
We will express [tex]\( f \)[/tex] as a function of [tex]\( \eta \)[/tex], [tex]\( M \)[/tex], [tex]\( U \)[/tex], and a proportionality constant [tex]\( k \)[/tex]:
[tex]\[ f = k \cdot \eta^a \cdot M^b \cdot U^c \][/tex]
### Step 1: Determine Dimensions of Each Quantity
1. Viscous Force [tex]\( f \)[/tex]:
- Dimension: [tex]\([f] = \text{MLT}^{-2}\)[/tex]
2. Coefficient of Viscosity [tex]\( \eta \)[/tex]:
- Dimension: [tex]\([\eta] = \text{ML}^{-1}\text{T}^{-1}\)[/tex]
3. Radius [tex]\( M \)[/tex]:
- Dimension: [tex]\([M] = \text{L}\)[/tex]
4. Speed [tex]\( U \)[/tex]:
- Dimension: [tex]\([U] = \text{LT}^{-1}\)[/tex]
### Step 2: Set Up Dimensional Equation
We need the dimensions on both sides of the equation [tex]\( f = k \eta^a M^b U^c \)[/tex] to be consistent. Thus,
[tex]\[ [f] = [k \eta^a M^b U^c] \][/tex]
Substituting the dimensions, we get:
[tex]\[ \text{MLT}^{-2} = [k] \cdot (\text{ML}^{-1}\text{T}^{-1})^a \cdot (\text{L})^b \cdot (\text{LT}^{-1})^c \][/tex]
### Step 3: Break Down the Dimensions
Combining the dimensions, we get:
[tex]\[ \text{MLT}^{-2} = \text{M}^a \cdot \text{L}^{-a} \cdot \text{T}^{-a} \cdot \text{L}^b \cdot \text{L}^c \cdot \text{T}^{-c} \][/tex]
Simplifying the dimensions, we have:
[tex]\[ \text{MLT}^{-2} = \text{M}^a \cdot \text{L}^{-a+b+c} \cdot \text{T}^{-a-c} \][/tex]
### Step 4: Equate the Exponents
Equating the exponents for [tex]\( \text{M} \)[/tex], [tex]\( \text{L} \)[/tex], and [tex]\( \text{T} \)[/tex] on both sides, we get three equations:
1. For mass (M):
[tex]\[ 1 = a \][/tex]
2. For length (L):
[tex]\[ 1 = -a + b + c \][/tex]
3. For time (T):
[tex]\[ -2 = -a - c \][/tex]
### Step 5: Solve the System of Equations
From the first equation:
[tex]\[ a = 1 \][/tex]
Substituting [tex]\( a = 1 \)[/tex] in the third equation:
[tex]\[ -2 = -1 - c \][/tex]
[tex]\[ -1 - c = -2 \][/tex]
[tex]\[ c = 1 \][/tex]
Substituting [tex]\( a = 1 \)[/tex] and [tex]\( c = 1 \)[/tex] in the second equation:
[tex]\[ 1 = -1 + b + 1 \][/tex]
[tex]\[ 1 = b \][/tex]
### Step 6: Write the Final Formula
Substituting [tex]\( a = 1 \)[/tex], [tex]\( b = 1 \)[/tex], and [tex]\( c = 1 \)[/tex] into our original expression [tex]\( f = k \eta^a M^b U^c \)[/tex], we obtain:
[tex]\[ f = k \eta^1 M^1 U^1 \][/tex]
Therefore, the formula for the viscous force [tex]\( f \)[/tex] is:
[tex]\[ f = k \eta M U \][/tex]
where [tex]\( k \)[/tex] is a dimensionless proportionality constant.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.